FENOMENA URBAN HEAT ISLAND DI KOTA BANDUNG - Hamdani, Gildan Kantona; Rikumahu, Viona Dika; Putra, Fabio Esa; Uny, Chivilya (STKIP PGRI Situbondo, 2025)
The Urban Heat Island (UHI) phenomenon is defined as an increase in temperature in urban areas that is higher than the temperature in surrounding rural areas. In Indonesia, Bandung Municipality is one of the urban areas that is indicated to experience an increase in surface temperature due to the rapid pace of development. Therefore, this study will review the existing literature on the phenomenon of UHI. Subsequently, the phenomenon is identified through an examination of the spatial pattern of surface temperature and vegetation density values in Bandung Municipality. The analysis was conducted using Landsat 8 images, which were then processed with a GIS program to generate Land Surface Temperature (LST) maps and Normalized Difference Vegetation Index (NDVI) maps. The results of this study indicate that Bandung Municipality experienced an increase in surface temperature from 2018 to 2022. This finding aligns with the observed reduction in vegetation density in Bandung City in 2022. Additionally, the rise in population and anthropogenic activities in urban areas contribute to the observed increase in surface temperature in Bandung Municipality.